2007
DOI: 10.1039/b605531c
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystalline dendrimers

Abstract: In recent years, there has been an increasing interest in the field of liquid crystalline dendrimers. Such a fast development is, among other things, driven by the multiple possibilities offered by combining the mesomorphic properties of single mesogenic subunits with the supermolecular and versatile architectures of dendrimers to yield a new class of highly functional materials. The induction and the control of the mesomorphic properties (phase type and stability) in dendrimers can be achieved by a dedicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(110 citation statements)
references
References 138 publications
3
105
0
Order By: Relevance
“…[11] After the substitution, TEM experiments (observations on a carbon-coated copper grid) showed that the diameter of the core of the particles remained unchanged (21 ± 5 Å) (Fig. S1, Supporting Information), which was also confirmed by the unchanged plasmon UV-vis band after substitution (Fig.…”
Section: This Paper Is Dedicated To Marc Drillon On the Occasion Of supporting
confidence: 57%
“…[11] After the substitution, TEM experiments (observations on a carbon-coated copper grid) showed that the diameter of the core of the particles remained unchanged (21 ± 5 Å) (Fig. S1, Supporting Information), which was also confirmed by the unchanged plasmon UV-vis band after substitution (Fig.…”
Section: This Paper Is Dedicated To Marc Drillon On the Occasion Of supporting
confidence: 57%
“…However, this possibility must be ruled out considering that all the compounds that show rectangular columnar mesomorphism contain a poly(benzyl ether) dendron. 61,63 This dendron is known to promote columnar mesomorphism. 61,63 From the observed reflections, the 2D space groups for the rectangular columnar phases of compounds 2, 3, 5, and 7 can be deduced on the basis of the extinction rules that govern the space-groups attribution.…”
Section: 5mentioning
confidence: 99%
“…61,63 This dendron is known to promote columnar mesomorphism. 61,63 From the observed reflections, the 2D space groups for the rectangular columnar phases of compounds 2, 3, 5, and 7 can be deduced on the basis of the extinction rules that govern the space-groups attribution. 70 For 5 and 7 this attribution can only .…”
Section: 5mentioning
confidence: 99%
“…[12,13] Liquid-crystal dendrimers in comparison with low molecular weight mesogens provide a highly congested environment that restricts the mobility of the mesogenic units of the molecules and thus favours enhancement of the microsegregation that leads to a finer control of mesomorphic behaviour. [14,15] The structure and generation of the dendrimer and the chemical nature of the mesogenic units introduced determine the liquid-crystal properties of the material. [16] Organic electronics and the possibilities that arise from the fabrication of new devices such as organic light-emitting diodes, [17][18][19][20] organic field effect transistors [21,22] and organic photovoltaics [23][24][25] based on organic molecules have driven a promising field of research of new multifunctional materials that can compete with the already established polycrystalline inorganic materials.…”
Section: Introductionmentioning
confidence: 99%